Perspective of new innovative biogas technology policy implementation for sustainable development in India. (December 2021) - Aggarwal, R.K.; Chandel, Shyam Singh; Yadav, Priya; Khosla, Atul
Abstract: The energy costs have increased substantially in recent years due to widespread development in India. Vast agro and animal waste resources are available which can easily be harnessed for biogas production economically Recently, there has been a renewed interest to revive the National biogas programme to meet the ever-increasing energy demand. India has set a target of reducing oil imports by 10% through the increased use of natural gas contribution in the current energy mix of 6.5%–15% by 2022. In this study the new Indian biogas policy initiatives for biogas production, new plant designs are presented along with a comparative analysis of the policy with similar policies of selected countries. The flaws in the past implementation of Indian bio-gas programmes, biogas technology as per most recent data along with identifying gaps in the new Indian biogas policy, are presented. A strategy is outlined to utilize large quantities of available food, agro and animal waste resources for a sustainable bio-gas policy as per UN sustainable development goal numbers 1, 7 and 13 . The need for a sustainable biogas policy is emphasized to provide a clean fuel for cooking, heating, and lighting with focus on rural poor worldwide. Graphical abstract: Strategy for a novel sustainable bio-gas policyThe flaws in the past implementation of Indian bio-gas programmes, current status of biogas technology as per most recent data along with identifying gaps in the new Indian biogas policy, are presented. Based on the comparative analysis of new Indian policy with similar policies of selected countries, a strategy is outlined to utilize vast quantities of available agro, food and animal resources for a sustainable bio-gas policy as per UN sustainable development goal numbers 1, 7 and 13, to provide clean bio-gas fuel to the poor worldwide. Image 1 Highlights: New Indian Biogas Policy Perspectives are presented. Biogas policies of selected countries are critically analyzed. . Policy concerns of propagating liquid petroleum gas in rural areas, are identified. Strategy is outlined for effective implementation of new sustainable biogas policy.